Do we have serological evidences that chilblain‐like lesions are related to SARS‐CoV‐2? A review of the literature. Issue 6 (14th September 2020) - Balestri, Riccardo; Magnano, Michela; Rizzoli, Laura; Rech, Giulia
Abstract: The outbreak of chilblain‐like lesions (CLL) coincidentally to the COVID‐19 pandemic is a topic of great concern. SARS‐CoV‐2 was initially hypothesized as the etiologic agent of CLL, but, since nasopharyngeal swabs seldom resulted positive, dermatologists' attention focused on the search for specific SARS‐CoV‐2 antibodies. Many papers were published contemporarily on this topic, reporting limited case series. We reviewed the English literature up to the first July 2020 and, excluding single case reports, we considered 13 studies that serologically investigated 220 patients. The presence of specific antibodies was detected in 18 subjects (8.2%): isolated IgA were found in 6 patients, IgA and IgG in 1, isolated IgG in 5, and IgM in 2. In 4 patients, isotypes were not specified. Our review demonstrated a high prevalence of negative serological results in CLL: antibodies were observed only in a few patients, that are even less excluding those with positive IgA, not clearly involved in the pathogenesis of the disease. In conclusion, although it is still uncertain whether CLL are related to SARS‐CoV‐2 infection, patients affected by CLL seem not to be prone to shedding the virus, hence, if they are asymptomatic, we can reassure them, thus avoiding hospital referral.